Analysing the effect of CSF inflammatory proteins on stroke severity in people with varying severities of Alzheimer's disease - Chan, Shawn Kiat Zhong (Nanyang Technological University, 2023)
Stroke is a debilitating condition that affects ~25% of the world’s population with many risk factors such as Alzheimer’s Disease (AD). In stroke, inflammatory responses contribute to neuronal cell death and worsen stroke severity among patients. Here, 13 different CSF inflammatory proteins: TNFR1, TNFR2, TGFβ1, TGFβ2, TGFβ3, IL21, IL6, IL7, IL10, TNFα, ICAM1 and VCAM1 were analysed among 385 participants of varying degrees of AD to investigate their effects on stroke severity. The effects of age and gender on stroke severity were also analysed in this study. Multiple linear regression analyses were done on 3 different groups (CD Global Score 0, 0.5 and 1). Age and gender were found to positively influence stroke severity in the AD brain. Among the CSF inflammatory proteins, TNFα and IL7 were found to have the strongest effects, with TNFα positively influencing stroke severity in the AD brain and IL7 negatively influencing stroke severity in the AD brain. IL6, IL10, TGFB3, CRP and ICAM1 were found to negatively influence stroke severity in the AD brain while IL21, TGFB1, TGFB2 and VCAM1 were found to positively influence stroke severity in the AD brain. However, TNFR1 and TNFR2 were found to have small and not significant effects on stroke severity in the AD brain. This study suggests that CSF inflammatory proteins are related to stroke severity and sheds some light on important CSF inflammatory proteins such as TNFα and IL7 for future research as possible stroke therapeutics.